Temperature- and pH-sensitive wearable materials for monitoring foot ulcers - Salvo P (Dove Medical Press, 2017)
Pietro Salvo,1,2 Nicola Calisi,1 Bernardo Melai,1 Valentina Dini,3 Clara Paoletti,1 Tommaso Lomonaco,1 Andrea Pucci,1 Fabio Di Francesco,1 Alberto Piaggesi,4 Marco Romanelli3 1Department of Chemistry and Industrial Chemistry, University of Pisa, 2Institute of Clinical Physiology, National Council of Research, 3Wound Healing Research Unit, Department of Dermatology, University of Pisa, 4Diabetic Foot Section, Department of Medicine, University of Pisa, Pisa, Italy Abstract: Foot ulcers account for 15% of comorbidities associated with diabetes. Presently, no device allows the status of foot ulcers to be continuously monitored when patients are not hospitalized. In this study, we describe a temperature and a pH sensor capable of monitoring diabetic foot and venous leg ulcers developed in the frame of the seventh framework program European Union project SWAN-iCare (smart wearable and autonomous negative pressure device for wound monitoring and therapy). Temperature is measured by exploiting the variations in the electrical resistance of a nanocomposite consisting of multiwalled carbon nanotubes and poly(styrene-b-(ethylene-co-butylene)-b-styrene). The pH sensor used a graphene oxide (GO) layer that changes its electrical potential when pH changes. The temperature sensor has a sensitivity of ~85 Ω/°C in the range 25°C–50°C and a high repeatability (maximum standard deviation of 0.1% over seven repeated measurements). For a GO concentration of 4 mg/mL, the pH sensor has a sensitivity of ~42 mV/pH and high linearity (R2=0.99). Keywords: diabetic foot ulcer, wearable sensors, wound temperature, wound pH